The ART of decision making: Retreatment with transarterial chemoembolization in patients with hepatocellular carcinoma1. Issue 6 (3rd May 2013) - Sieghart, Wolfgang; Hucke, Florian; Pinter, Matthias; Graziadei, Ivo; Vogel, Wolfgang; Müller, Christian; Heinzl, Harald; Trauner, Michael; Peck‐Radosavljevic, Markus
Abstract We aimed to establish an objective point score to guide the decision for retreatment with transarterial chemoembolization (TACE) in patients with hepatocellular carcinoma (HCC). In all, 222 patients diagnosed with HCC and treated with multiple TACE cycles between January 1999 and December 2009 at the Departments of Gastroenterology/Hepatology of the Medical Universities of Vienna (training cohort) and Innsbruck (validation cohort) were included. We investigated the effect of the first TACE on parameters of liver function and tumor response and their impact on overall survival (OS, log rank test) and developed a point score (ART score: Assessment for Retreatment with TACE) in the training cohort (n = 107, Vienna) by using a stepwise Cox regression model. The ART score was externally validated in an independent validation cohort (n = 115, Innsbruck). The increase of aspartate aminotransferase (AST) by >25% (hazard ratio [HR] 8.4; P < 0.001), an increase of Child‐Pugh score of 1 (HR 2.0) or ≥2 points (HR 4.4) (P < 0.001) from baseline, and the absence of radiologic tumor response (HR 1.7; P = 0.026) remained independent negative prognostic factors for OS and were used to create the ART score. The ART score differentiated two groups (0‐1.5 points; ≥2.5 points) with distinct prognosis (median OS: 23.7 versus 6.6 months; P < 0.001) and a higher ART score was associated with major adverse events after the second TACE (P = 0.011). These results were confirmed in the external validation cohort and remained significant irrespective of Child‐Pugh stage and the presence of ascites prior the second TACE. Conclusion: An ART score of ≥2.5 prior the second TACE identifies patients with a dismal prognosis who may not profit from further TACE sessions. (HEPATOLOGY 2013;57:2261–2273)